Proopiomelanocortin (POMC) expression and conditioned place aversion during protracted withdrawal from chronic intermittent escalating-dose heroin in POMC-EGFP promoter transgenic mice - Niikura, Keiichi (2013)
In heroin-dependent individuals, the drive to avoid or ameliorate the negative affective/emotional state associated with the discontinuation of heroin contributes to the chronic relapsing nature of the disease. Here, we investigate changes in proopiomelanocortin (POMC) expression at three time points across an extended period of heroin withdrawal in a clinically relevant rodent model of addiction using conditioned place aversion (CPA) in POMC-EGFP bacterial artificial chromosome transgenic mice. Neurons expressing POMC-EGFP were found in the medial nucleus of amygdala (MeA), basomedial amygdala (BMA) and dentate gyrus of hippocampus (DG), as well as the arcuate nucleus of hypothalamus (ARC). Heroin-treated mice displayed robust CPA after acute spontaneous withdrawal (12h), which persisted across the extended (14d) withdrawal period. After 12h withdrawal, heroin-treated mice showed lower signal intensity of POMC-EGFP positive cells in the ARC, higher levels of POMC mRNA in the amygdala but lower levels in the hippocampus than saline controls. After 7d withdrawal, heroin-treated mice showed fewer POMC-EGFP positive cells in the MeA and lower POMC mRNA in the amygdala than saline controls. After extended (14d) withdrawal, heroin-treated mice showed more POMC-EGFP positive cells in BMA and DG, increased intensity of POMC-EGFP signal in DG, and higher POMC mRNA levels in hippocampus compared to controls. Our results show dynamic changes in POMC in hypothalamic and extra-hypothalamic regions that may contribute to the negative affective/emotional state of heroin withdrawal shown by CPA from acute to extended periods of heroin withdrawal.